MANAJEMEN ASUHAN KEBIDANAN KOMPLEKS PADA BAYI BARU LAHIR DENGAN ASFIKSIA RINGAN DI BPM SURATMI KOTA BATAM TAHUN 2022 - Asa Bayuana; Sri Rizki Ayu Nova Dinata; Helfia Gustin; Rohaida Rohaida; Rosnaini Rosnaini; Vebby Ayu Saphira; Suratmi Suratmi; Nurlisyah Wati Riski; Putri Esmariantika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Asphyxia neonatorum is a condition in which the baby cannot breathe spontaneously and regularly immediately after birth. Asphyxia occupies the number 3 mortality rate in newborns with a rate of 23%. This task aims to understand midwifery care in complex cases of newborns with asphyxia. This case study uses a descriptive method with a case study approach and reference collection. Care is carried out by clearing the airway, stimulating respiratory reflexes, and maintaining body temperature. Based on the results of the case study, it can be concluded that BY. X with midwifery care of newborns with asphyxia went well marked by a Normal Apgar Score, the conclusion is the importance of assessing the Apgar Score in newborns with asphyxia with action in accordance with evidence based.